PENGARUH KEBIJAKAN LOAN TO VALUE (LTV) DAN REPAYMENT CAPACITY TERHADAP KUALITAS KREDIT PEMILIKAN RUMAH (KPR) PADA PT. BANK NEGARA INDONESIA (PERSERO)TBK KANTOR CABANG PALU - Indriani, Indriani (Katalogis, 2015)
This research aims to know and to analyze the effect of Loan to Value and Repayment Capacity on Credit Quality of Mortgage Loan at PT Bank Negara Indonesia (Persero) Tbk, Palu Branch Office. Population of this research covers 1.297 debtoers and 149 out of them have been chosen as the sample for this research using purposive sampling method. Based an the result of multiple linear regression show that: (1) LTV and Repayment Capacity simultaneously perform significant effect on credit quality of mortgage loan at PT. Bank Negara Indonesia (persero) Tbk Kantor Cabang Palu. (2) LTV performs significant negative effect on credit quality of mortgage loan at PT. Bank Negara Indonesia (persero) Tbk, Palu Branch Office. (3) Repayment Capacity partially performs positive effect on credit of mortgage loan at PT. Bank Negara Indonesia (persero) Tbk, Palu Branch Office. Determination Confficient (R2) 0.143 means that only 14.3% is affected by other variables that are not investigated in this research.